2010
DOI: 10.1017/s0022215110002434
|View full text |Cite
|
Sign up to set email alerts
|

Modified arytenoid adduction for cancer-related unilateral vocal fold paralysis

Abstract: Modified arytenoid adduction is an effective and reliable medialisation technique which can restore satisfactory voice quality, prevent aspiration and lead to a better quality of life for patients with cancer-related unilateral vocal fold paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The 4 studies using this outcome all noted improvement, with a reduction of 6 points, 44 4.5 points, 12 1 point, 45 and 4.76 points 41 . Seven studies indicated improvement in dysphagia and/or aspiration as a percentage of the cohort without indication of a specific quantitative outcome measure 19,23,25,31–33 . In these studies, authors indicated that improvement was based on clinical assessment by the surgeon and/or speech pathologist after surgery at a defined interval, but specific methodology was not stipulated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4 studies using this outcome all noted improvement, with a reduction of 6 points, 44 4.5 points, 12 1 point, 45 and 4.76 points 41 . Seven studies indicated improvement in dysphagia and/or aspiration as a percentage of the cohort without indication of a specific quantitative outcome measure 19,23,25,31–33 . In these studies, authors indicated that improvement was based on clinical assessment by the surgeon and/or speech pathologist after surgery at a defined interval, but specific methodology was not stipulated.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies had sufficient data to be in the quantitative analysis of treatment success, which encompassed 293 subjects/medialization procedures. 19,25,27,[31][32][33][34][35][39][40][41] Only studies that reported subject-level outcome data stratified by procedure were included. An analysis of dysphagia outcomes from LR procedures could not be performed because just 7 subjects with dysphagia underwent LR in the studies.…”
Section: Quantitative Analysis Of Treatment Successmentioning
confidence: 99%
“…Since first described by Isshiki et al [9] in 1978, arytenoid adduction resulted in better correcting a large posterior glottal gap and vertical differences of the 2 vocal folds [10]. As the 3-dimensional movement of arytenoid was relatively complicated in phonation, the traditional Isshiki arytenoid adduction operation may generate unsatisfactory voice quality outcomes in some patients [6, 8]. Meanwhile, compared with medialization thyroplasty, the disadvantages of increase in overall complications and operating time also restricted the widespread of arytenoid adduction operation [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these operations demonstrate to be definitely superior over the others [6]. Injection laryngoplasty treatment for UVFP often do not guarantee long-term effectiveness and widespread acceptance, and the traditional Type I thyroplasty cannot effectively correct differences in the levels of the 2 vocal folds [6][7][8]. Since first described by Isshiki et al [9] in 1978, arytenoid adduction resulted in better correcting a large posterior glottal gap and vertical differences of the 2 vocal folds [10].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal rehabilitation period after UVFP is within one year after surgery, so timely and effective treatment may help patients to restore voice function. Many surgical treatments and voice training methods for UVFP have been reported for those who suffer from UVFP in a paramedian position and if they do not recover within 6 months, another surgery is needed, including intracordal injection, arytenoid adduction, laryngoplasty, transplantation or decompression of the RLN [10][11][12][13][14][15][16][17][18][19]. These surgeries could make the affected VF side move to the midline, promoting glottal closure and improving vocal function.…”
Section: Introductionmentioning
confidence: 99%